Endothermy and floral utilization of Cyclocephala caelestis (Coleoptera: Scarabaeoidea; Melolonthidae): a cloud forest endemic beetle. - Dieringer, Gregg; Reyes Castillo, Pedro; Lara, Manuel; Cabrera R, Leticia; Loya, Larisa (Instituto de Ecología, A.C., 1998)
A study of the pollination ecology of Magnolia tamaulipana and its specialized pollinator, Cyclocephala caelestís was conducted at the El Cielo Biosphere Reserve, Tamaulipas during the late spríng of 1996. Cychcaphala caelestis visited fiowers of M. tamaulipana most frequently after 2100 with males being more abundant than females. Wa report for the first time within the ganus, endothermy and thoracic temperatura regulation for C. caelestis. Thoracic temperature averaged 26.8°C ± SE = 0.3 with an excess temperatura of 4.7°C ± SE = 0.3. Males and females did not differ in mean thoracic temperatura. While within the flowers, beetles regulated their thoracic temperature índependently of ambient and floral temperaturas and were observed mating and feeding on petal tissue. Endothermy is probably important for mating and feeding activities which occur at night during cool temperatures. Petal tissue is thought to contain ethereal oils within which are dissolved chiral esters thet are responsible for floral odor and the attraction of Cyclocephala specíes. Petal and sepal tissue both contain high amounts of carbohydrata and protein, but petals contain 4x less fiber, which probably accounts for its preference as a food tissue by Cyclocephala.